UNVEILING BRAZIL: SOCIOECONOMIC AND POLITICAL REALITIES OF THE LATE '80S THROUGH BRÁULIO TAVARES' STUNTMIND - Araújo, Naiara Sales; Carneiro, Monica Fontenelle; Mugschl, Sonia Maria Correa Pereira (ARACÊ, 2024)
The present article aims to show how Brazilian Science Fiction provides an interesting reading of Brazil’s economic and political context and its social and cultural disturbances in the late 80s. With the end of the military regime, writers tended to explore the social context focusing on the contradictions of the process of modernization and its negative results for Brazilian society. In this context, writers did not hesitate to combine technology and cultural alienation in a Third World political perspective. By analyzing Bráulio Tavares’ “Stuntmind” it is possible to see his critique to the effects of globalization toward Brazilian culture, as well as toward Brazil’s political and economic development.